(untitled) (Research, Society and Development, 2017)
Purple Thrombocytopenia Idiopathic (PTI) is a blood disorder caused due to a hematological disorder characterized by a decrease in the number of circulating platelets in the blood. The aim of this study is to guide the dentist with care regarding the treatment of patients with PTI. A literature review was performed using the databases: PubMed and SciELO. In the buccal cavity it can cause petechiae, ecchymosis in the mucosa, spontaneous gingival bleeding, bleeding of superficial lesions and cuts, and may be spontaneous or caused by minor trauma. The dentist must understand and take care of the treatment of these patients, being important to carry out preventive actions and working with the philosophy of minimal intervention.